2010
DOI: 10.1080/10508611003608049
|View full text |Cite
|
Sign up to set email alerts
|

Attachment to God, Images of God, and Psychological Distress in a Nationwide Sample of Presbyterians

Abstract: Drawing broadly on insights from attachment theory, the present study outlines a series of theoretical arguments linking styles of attachment to God, perceptions of the nature of God (i.e., God imagery), and stressful life events with psychological distress. Main effects and potential stress-moderator effects are then evaluated using data from a nationwide sample of elders and rank-and-file members of the Presbyterian Church (U.S.A.). Key findings indicate that secure attachment to God is inversely associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
139
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(160 citation statements)
references
References 35 publications
(72 reference statements)
9
139
0
3
Order By: Relevance
“…First, in our longitudinal models there is a high correlation between T1 and T2 distress measures. Consequently only two baseline predictors-stressful events and secure attachment to God-are statistically significant at the p \ .01 level or greater, and given their established associations with T1 distress (Bradshaw et al 2010), it is not surprising that their added contributions to the predictive power of the change model are modest (only 2-3% of the overall variance explained). Second, studies have demonstrated that effect sizes, as well as the overall predictive power of statistical models, can depend upon the number of variables that influence the given outcome under study (Ahadi and Diener 1989).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, in our longitudinal models there is a high correlation between T1 and T2 distress measures. Consequently only two baseline predictors-stressful events and secure attachment to God-are statistically significant at the p \ .01 level or greater, and given their established associations with T1 distress (Bradshaw et al 2010), it is not surprising that their added contributions to the predictive power of the change model are modest (only 2-3% of the overall variance explained). Second, studies have demonstrated that effect sizes, as well as the overall predictive power of statistical models, can depend upon the number of variables that influence the given outcome under study (Ahadi and Diener 1989).…”
Section: Discussionmentioning
confidence: 99%
“…To be sure, the stress-moderating role of other facets of religiousness and spirituality, such as religious coping styles and practices, has been examined in prior work (Tix and Frazier 1998;Ellison et al 2001;Fabricatore et al 2004). Yet, with the partial exception of the Bradshaw et al (2010) study, to our knowledge this issue has been neglected in the emerging research on attachment to God and its implications for mental health.…”
Section: Theoretical and Empirical Backgroundmentioning
confidence: 99%
“…Studies have found secure attachment to and intimacy with God to be inversely associated with psychological distress and psychopathology (Bradshaw et al 2008;Bradshaw et al 2010), and positively associated with greater resilience after perceived negative events (Ellison et al 2014). Anxious attachment, in contrast, was positively correlated with psychiatric symptoms such as general and social anxiety, obsession, and compulsion (Ellison et al 2014).…”
Section: Religion and Attachment Theorymentioning
confidence: 99%
“…Secure attachment to God is inversely associated to distress (Bradshaw, Ellison, & Marcum, 2010), depression (Sim & Yow, 2011), and has significant effects on grief and stress-related growth (Kelley & Chan, 2012). While specifically addressing faith and God in treatment may be outside the comfort zone of many therapists, it seems that that decision is one that should be in the hands of the client many clients desire integrating their faith into treatment (Rose, Westefeld, & Ansley, 2001).…”
Section: Interventions For Crisis Of Faithmentioning
confidence: 99%